Microaerobic Digestion of Low-Biodegradable Sewage Sludge: Effect of Air Dosing in Batch Reactors - Raffaele Morello (Sustainability, 2021)
The adoption of prolonged solid retention times during the biological treatment of urban wastewaters is a well-known strategy to reduce sewage sludge production. However, it also results in the production of a biological sludge with low percentages of biodegradable organic matter, also characterized by high humification degrees, which may hamper the anaerobic digestion treatment aimed at sludge stabilization. To accelerate the hydrolytic stage, the application of microaerobic conditions during the anaerobic digestion of low-biodegradable sewage sludge was investigated in this study. In particular, six bio-methanation tests of a real sewage sludge were carried out, introducing air in the bioreactors with doses ranging between 0 and 16.83 L air/kg VSin d, in order to evaluate the air dosage that optimizes the biomethane production and organic matter degradation. Notably, the lower air loading rates investigated in this study, such as 0.68 and 1.37 L air/kg VSin d, led to an increase in methane production of up to 19%, due to a higher degradation of total lipids and proteins. In addition, these microaerobic conditions also resulted in a decrease in the sludge humification degree and in lower volatile fatty acid accumulation.